The prospect of micropropagating Gonystylus bancanus (Miq.) Kurz, a tropical peat swamp forest timber species through tissue culture technique - review - Grippin, Akeng; Nor Aini, Ab Shukor; Nor Akhirrudin, Mahmud; Hazandy, Abdul Hamid; Sures Kumar, Muniandy; Ismail, Parlan (Czech Academy of Agricultural Sciencesbraun@uzpi.cz, 2018)
Gonystylus bancanus (Miquel) Kurz is one of the most valuable timber species in tropical peat swamp forest. Its timber is widely used for furniture, decorative cabinets and interior decoration. Due to its higher demand, G. bancanus continues to be harvested which leads to its disappearance in the wild. This is worsened by the fact that germination rates in the wild are very poor due to rapid insect and fungal infestation. Even though vegetative propagation via stem cuttings has been successful, proper protocols on tissue culture need to be explored as a viable way of mass production of a large number of planting stock in a relatively shorter time for forest rehabilitation and enrichment planting purposes.